2014
DOI: 10.1177/0954410014526708
|View full text |Cite
|
Sign up to set email alerts
|

An analytical investigation of stator lean on rotor–stator interaction noise

Abstract: This paper concentrates on the noise reduction effect of stator lean in rotor-stator interaction. The compressor with a serial stator-blade lean angle has been employed to acoustically test and numerically calculate. The experiment results show that stator-leaned positive has better effect on noise reduction than leaned negative; the tone noise is determinant on total sound pressure level, and the lean angle of the stator should exceed 10 . Based on the results of unsteady calculation about the compressor, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…With the rapid development of computers and computational method, the numerical simulation makes even more attractive technique to research the inner flow in pumps. Several numerical studies have been reported in the technical literature on rotor and stator interaction [9][10][11]. For example, Javadi [9] investigated the precessing helical vortex in a conical diffuser, with rotor-stator interaction, which showed the rotor-stator interaction is necessary to reproduce the physics of the helical vortex in the draft tube.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of computers and computational method, the numerical simulation makes even more attractive technique to research the inner flow in pumps. Several numerical studies have been reported in the technical literature on rotor and stator interaction [9][10][11]. For example, Javadi [9] investigated the precessing helical vortex in a conical diffuser, with rotor-stator interaction, which showed the rotor-stator interaction is necessary to reproduce the physics of the helical vortex in the draft tube.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Javadi [9] investigated the precessing helical vortex in a conical diffuser, with rotor-stator interaction, which showed the rotor-stator interaction is necessary to reproduce the physics of the helical vortex in the draft tube. Liu [10] presents an analytical investigation of stator lean on rotor-stator interaction noise in the compressor, which indicated that stator-leaned positive has better effect on noise reduction than leaned negative. Rodriguez [11] presents a theoretical analysis that allows us to describe the characteristics in the frequency domain of the vibration originated with the rotor-stator interaction in centrifugal pump turbine.…”
Section: Introductionmentioning
confidence: 99%